2015
DOI: 10.1002/adma.201501729
|View full text |Cite
|
Sign up to set email alerts
|

Rapid 3D Extrusion of Synthetic Tumor Microenvironments

Abstract: Solid tumors house an assortment of complex and dynamically changing microenvironments in which signaling events between multiple cell types are known to play a critical role in tumor progression, invasion, and metastasis. To deepen our understanding of this biology, it is desirable to accurately model these structures in vitro for basic studies and for drug screening; however, current systems fall short of mimicking the complex organization of cells and matrix in vivo. Here we demonstrate the generation of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 27 publications
0
94
0
1
Order By: Relevance
“…In another study, drug inhibition of tumor cell-macrophage paracrine interactions was analyzed using co-culture of breast adenocarcinoma cells and macrophages in alginate hydrogel fibers. Gefitinib, an EGFR inhibitor, and a Rac1 inhibitor were both able to impair macrophage migration to cancer cells, and the 3D cell distribution and cancer cell-macrophage ratio affected drug responses 76 . Although generally faster than in vivo models, 3D tumor models for drug testing typically require increased processing time relative to 2D cell monolayers.…”
Section: Biomaterials To Create 3d Tumor Modelsmentioning
confidence: 99%
“…In another study, drug inhibition of tumor cell-macrophage paracrine interactions was analyzed using co-culture of breast adenocarcinoma cells and macrophages in alginate hydrogel fibers. Gefitinib, an EGFR inhibitor, and a Rac1 inhibitor were both able to impair macrophage migration to cancer cells, and the 3D cell distribution and cancer cell-macrophage ratio affected drug responses 76 . Although generally faster than in vivo models, 3D tumor models for drug testing typically require increased processing time relative to 2D cell monolayers.…”
Section: Biomaterials To Create 3d Tumor Modelsmentioning
confidence: 99%
“…In addition to single tube structures, more diverse geometries mimicking more biomimetic structures can be generated by changing the design of microfluidic devices. Grolman et al demonstrated the generation of hollow microfibers in “straight,” “serpentine,” and “helically packed” architectures by adding an extra gelating outer flow (CaSO 4 solution) . Cheng et al developed a capillary‐based coaxial microfluidic device for the fabrication of perfusable microfibers ( Figure A) .…”
Section: Engineering Approaches On Fabricating Perfusable Microchannementioning
confidence: 99%
“…Gorlman et al modeled the tumor microenvironment by coculturing human breast adenocarcinoma cells and mouse macrophage cells in extruded hollow microfibers in different patterned geometries. The results showed the channel geometries could affect macrophage‐tumor cell signaling . Wong et al demonstrated that chemotherapeutic drug in different formulation performed different transendothelial transport ability, distribution, and function in a vascularized tumor model in vitro …”
Section: Applications Of Biomimetic Vascularizationmentioning
confidence: 99%
“…3D printing of cells most often uses hydrogel encapsulation of cells to form a 3D structure[217]–[220]. Yoo and colleagues 3D printed multi-layered collagen hydrogels which contained layers of human skin fibroblasts and keratinocytes[218].…”
Section: Microengineering 3d Biomaterials To Study and Direct Cellmentioning
confidence: 99%